Utility Values for Advanced Soft Tissue Sarcoma Health States from the General Public in the United Kingdom. (17th March 2013) - Guest, Julian F.; Sladkevicius, Erikas; Gough, Nicholas; Linch, Mark; Grimer, Robert
Abstract : Soft tissue sarcomas are a rare type of cancer generally treated with palliative chemotherapy when in the advanced stage. There is a lack of published health utility data for locally advanced "inoperable"/metastatic disease (ASTS), essential for calculating the cost-effectiveness of current and future treatments. This study estimated time trade-off (TTO) and standard gamble (SG) preference values associated with four ASTS health states (progressive disease, stable disease, partial response, complete response) among members of the general public in the UK (n = 207 ). The four health states were associated with decreases in preference values from full health. Complete response was the most preferred health state (mean utility of 0.60 using TTO). The second most preferred health state was partial response followed by stable disease (mean utilities were 0.51 and 0.43, respectively, using TTO). The least preferred health state was progressive disease (mean utility of 0.30 using TTO). The utility value for each state was significantly different from one another (P < 0.001 ). This study demonstrated and quantified the impact that different treatment responses may have on the health-related quality of life of patients with ASTS.